Government Medical Officers' Association's proposed COVID-19 Exit Strategy for Sri Lanka - Anuruddha Padeniya; Samantha Ananda; Nimani de Lanerolle; Bhumini Karunarathna; Naveen De Soysa; Senal Fernando; Haritha Aluthge; Chandana Dharmaratna; Sarada Kannangara; Kiyara Fernando; Prasad Colombage (College of Community Physicians of Sri Lanka, 2020)
No abstract available